Reality, Fiction and History in George Orwell’s novel 1984 and Kasëm Trebeshina’s Odin Mondvalsen - Turku, Marsela (Mediterranean Journal of Social Sciences, 2011)
In the recent years one of the major contributions to the distinction between fiction and real world has been provided by thetheory and semantics of possible worlds, whose bases is the idea that reality is a universe composed of a plurality of distinct worlds. Awriter of fiction usually â€œdrawsâ€ his material from the reality, from the models and the entities provided by the actual world, realisticfiction, in particular, depends on â€œmimetic communication to create possible worlds. This paper deals with two novels that treat the sametopic (â€œthe transformation of the society and of the human being under the communist dictatorshipâ€) but with an enormous difference,Orwell based his book almost entirely on his fictitious reality and imagination whereas Trebeshina has experienced the regime and itsreality. Many scholars and critics have tried to find similarities between Orwellâ€™s and Trebeshinaâ€™s vision of reality and even in their lifeexperiences. This paper deals with the construction of fiction, reality, the role of history and the similarities and differences presented onTrebeshinaâ€™s Odin Mondvalsen and Orwellâ€™s 1984.